Embryo movement is more frequent in avian brood parasites than birds with parental reproductive strategies. Issue 1961 (27th October 2021) - McClelland, Stephanie C.; Reynolds, Miranda; Cordall, Molly; Hauber, Mark E.; Goymann, Wolfgang; McClean, Luke A.; Hamama, Silky; Lund, Jess; Dixit, Tanmay; Louder, Matthew I. M.; Safari, Ignas; Honza, Marcel; et al.
Abstract : Movement of the embryo is essential for musculoskeletal development in vertebrates, yet little is known about whether, and why, species vary. Avian brood parasites exhibit feats of strength in early life as adaptations to exploit the hosts that rear them. We hypothesized that an increase in embryonic movement could allow brood parasites to develop the required musculature for these demands. We measured embryo movement across incubation for multiple brood-parasitic and non-parasitic bird species. Using a phylogenetically controlled analysis, we found that brood parasites exhibited significantly increased muscular movement during incubation compared to non-parasites. This suggests that increased embryo movement may facilitate the development of the stronger musculoskeletal system required for the demanding tasks undertaken by young brood parasites.